Analysis of Psychological Conditions Reviewed from Mental Toughness, Anxiety, and Self-Confidence in Bridge Athletes in Jambi Province - Nuraini, Tryna; Widowati, Atri; Daya, Wawan Junresti (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study focuses on the psychological condition of bridge athletes in Jambi Province, highlighting three main aspects: mental toughness, anxiety, and self-confidence. Bridge athletes often face pressure that can affect their performance, and this study aims to analyze how these psychological factors play a role in achieving achievements. This study uses a Mixed method between quantitative and qualitative methods. The sample consisted of 32 athletes, 3 coaches, 2 administrators of the Jambi Province Female Bridge Athletes. The instruments used were interviews and questionnaires. Initial findings indicate that many athletes experience difficulties in managing emotions and making decisions while competing. Based on the results of the descriptive analysis, the Standard deviation ranged from 0.69025 to 1.32698, indicating a fairly large variation in anxiety assessments among respondents. Overall, these results illustrate that despite the variation, the average level of anxiety of respondents tends to be low, with an overall average value of 68.7500 for the total score. This indicates that respondents are relatively not experiencing high anxiety.